Respuesta :
If you would like to know the equal expression to the x^6 - 9, you can do this using the following steps:
x^6 - 9 = (x^3)^2 - 3^2
(x^3)^2 = x^3 * x^3 = x^6
3^2 = 3 * 3 = 9
The correct result would be (x^3)^2 - 3^2.
x^6 - 9 = (x^3)^2 - 3^2
(x^3)^2 = x^3 * x^3 = x^6
3^2 = 3 * 3 = 9
The correct result would be (x^3)^2 - 3^2.
Answer:
[tex](x^{3})^{2} -3^{2}[/tex]
Step-by-step explanation:
we have
[tex]x^{6}-9[/tex]
we know that
[tex]x^{6}-9=(x^{3})^{2} -3^{2}[/tex]
Applying difference of square
[tex](x^{3})^{2} -3^{2}=(x^{3}+3)(x^{3}-3)[/tex]